METODE PEMBELAJARAN PADA EKSTRAKURIKULER DIDONG BANAN DI SMAN 8 TAKENGON ACEH TENGAH - Yulia Khairaawati (Grenek: Jurnal Seni Musik, 2019)
The results of the study prove that the Didong Banan in SMAN 8 Takengon Central Aceh has beenestablished since 2011 and was stopped in 2015 and reopened in 2016, Didong Banan extracurricularactivities have increased from year to year, at the beginning of the opening only students followed theexisting songs and now students can create their own songs through spontaneity, the method used indidong banan extracurricular is lecture method, project teaching method, discussion method, pono banoemethod, ward method, and dewey method. The rhythm pattern in Didong Banan is divided into three,namely rhythm of behavior, rhythmic rhythm, and rhythm of the pillow.